2022
DOI: 10.1088/2053-1591/ac7d9a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid composite based on conducting polymers and plasmonic nanomaterials applied to catalysis and sensing

Abstract: Combining plasmonic and semiconductors offers significant potential in creating sensing and photocatalytic devices. Nanocomposites including both metals and semiconductors can control the charge states in the metals that can enhance catalysis activity along with plasmon-enhanced spectroscopy. Here we demonstrate the use of conducting polymer materials with plasmonic nanomaterials to boost 5-fold plasmon-enhanced Raman scattering spectroscopy signal strength and support oxidation of target molecules through sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The second mechanism is that plasmonic hot electrons leap off the surface of the metal, and the hot holes that are left behind on the metal oxidize PATP to DMAB. It has been found that if a sufficiently enough external stimulus was introduced into the system, PATP would be oxidized to PNTP rather than oxidized to DMAB. , PATP on AgNPs/ZnO (Figure b) produces a Raman spectrum that replicates for PATP on only AgNPs with the spectrum assigned to DMAB. In contrast, when PATP is present on AgNPs/MoS 2 , the substrate prevents the formation of DMAB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second mechanism is that plasmonic hot electrons leap off the surface of the metal, and the hot holes that are left behind on the metal oxidize PATP to DMAB. It has been found that if a sufficiently enough external stimulus was introduced into the system, PATP would be oxidized to PNTP rather than oxidized to DMAB. , PATP on AgNPs/ZnO (Figure b) produces a Raman spectrum that replicates for PATP on only AgNPs with the spectrum assigned to DMAB. In contrast, when PATP is present on AgNPs/MoS 2 , the substrate prevents the formation of DMAB.…”
Section: Resultsmentioning
confidence: 99%
“…For PNTP on AgNP/ZnO, the Raman spectra of PNTP is preserved, with the Raman spectra (Figure c) showing the same features as recorded for PNTP (Figure a). In contrast, when MoS 2 is added forming ZnO/MoS 2 /AgNP, PNTP partially converts to DMAB with the Raman spectra showing peaks assigned to PNTP and DMAB. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations